Giant benign teratoma occupying the left hemithorax with pleural effusion: a rare presentation. Issue 9 (14th September 2020) - Bellido-Yarlequé, David; Meza, Kelly; Palacios, José; Cervera, Jorge; Anicama, Fernando
Abstract: Mature teratomas are the third most common mediastinal tumors. Giant teratoma in pediatric population is rare. A resection of giant benign teratoma in left hemithorax was performed in a 4-year-old patient. The computed tomography scan showed the presence of a large multiloculated mediastinal mass extending to the left pleural space and pleural effusion. The patient underwent total resection of the mediastinal mass via a median sternotomy associated to left anterior thoracotomy. Entry into the pleural space was performed through the sixth intercostal space to obtain safe visualization of the cavity and proceed to tumor excision. The collapsed left lung was re-expanded, and the patient was extubated. Despite the size and the surrounding structures of the teratoma, our preoperative preparation and surgical technique were effective and resulted in favorable recovery without complications and a posterior normal left lung function.